2015
DOI: 10.1007/s13595-015-0502-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular marker associated with a deleterious recessive anomaly in Eucalyptus grandis seedlings

Abstract: International audienceAbstract Key messageThe identification of an anomaly with deleterious effect and Mendelian segregation (3 normal: 1 abnormal) allowed the detection of a marker linked to a locus for the anomalous phenotype. This marker could be useful in marker-assisted breeding programs and for understanding this anomaly. ContextDue to the mixed mating systems in Eucalyptus genera, outcrossing populations exhibit low inbreeding depression (abnormalities). In this study, we identified a developmental anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
(67 reference statements)
1
10
0
Order By: Relevance
“…In a full-sib offspring from a controlled cross of Eucalyptus grandis performed at Suzano Papel and Celulose SA company, we observed an anomaly with a Mendelian segregation ratio of 3 normal: 1 abnormal seedling, indicating deleterious recessive alleles in homozygosis as the cause of the anomaly, as described in a previous study (Fuchs et al 2015). Our previous work showed that the abnormal seedlings died within a few months and presented some peculiar characteristics, including branching, reduced height, reduced individual leaf area, and leaf shape modifications.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…In a full-sib offspring from a controlled cross of Eucalyptus grandis performed at Suzano Papel and Celulose SA company, we observed an anomaly with a Mendelian segregation ratio of 3 normal: 1 abnormal seedling, indicating deleterious recessive alleles in homozygosis as the cause of the anomaly, as described in a previous study (Fuchs et al 2015). Our previous work showed that the abnormal seedlings died within a few months and presented some peculiar characteristics, including branching, reduced height, reduced individual leaf area, and leaf shape modifications.…”
Section: Introductionsupporting
confidence: 82%
“…Our previous work showed that the abnormal seedlings died within a few months and presented some peculiar characteristics, including branching, reduced height, reduced individual leaf area, and leaf shape modifications. We subsequently repeated the crossings to confirm the results obtained in Fuchs et al (2015) and included a Sequence Characterized Amplified Region (SCAR), a PCR-based marker associated with these morphological effects. In the present study, we evaluated plants at 4 months of age, a period at which the symptoms are more evident, enabling us to correctly distinguish phenotypes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The development of molecular markers for Eucalyptus species improved dramatically after the complete sequencing of its nuclear genome (nDNA) (Myburg et al 2014, Fuchs et al 2015. Currently, microsatellite markers (SSRs) are widely used in.…”
Section: Andrade Et Almentioning
confidence: 99%
“…Plant breeding programs have used molecular markers, directly and indirectly, to assist breeders in selecting genes of agricultural or forestry interest, by characterizing and identifying clones (parental and phylogeny tests), as well as planning crosses (FUCHS et al, 2015;VAILLANCOURT et al, 1998). BRONDANI et al (1998) listed a few comparative advantages of these genetic markers regarding co-dominance inheritance, such as multiallelism.…”
Section: Introductionmentioning
confidence: 99%